ALA glossary of library and information science (ALA editions, an imprint of the American Library Association, 2013)
The ALA Glossary of Library and Information Science presents a thorough yet concise guide to the specific words that describe the materials, processes and systems relevant to the field of librarianship. Written by a panel of experts from across the LIS world, and updated to include the latest technology- and internet-related terms, this handy book will become an essential part of every library's and librarian's reference collection and will also be a blessing for LIS students and recent graduates.